Role of zinc in inducing resistance in rice to whitebacked planthopper (Sogatella furcifera) under field conditions - Tripathy, Seema; Rath, Ladu Kishore (The Indian Journal of Agricultural Sciences, 2020)
The study on influence of Zn applied in forms of fertilizer formulations was carried out against whitebacked planthopper (WBPH) [Sogatella furcifera (Horvath)] infesting rice under field conditions during kharif 2016, summer 2016-17 and kharif 2017 in the Central Research Farm, College of Agriculture, Odisha University of Agriculture and Technology, Bhubaneswar. It was revealed that application of zinc to rice crop was instrumental in curbing the WBPH population. Basal application of Zn EDTA @ 40 kg/ha along with its foliar spray@ 0.8%, twice at 30 and 45 days after transplanting (DAT) (T6) was the best treatment in reducing the number of WBPH population over seasons as well as in increasing the grain yield. The next better treatment was T7 (ZnSO4 basal @ 25 kg/ha +Zn EDTA foliar spray @ 0.8% twice at 30 and 45 DAT) which also reduced the WBPH population substantially. From the entire study, it was inferred that reduction in WBPH population in various Zn supplementations as compared to control may be attributed to influence of Zn on rice plant physiology. Uptake of zinc definitely altered the nutritional status of rice plant as a result of which the population build up of WBPH on rice was minimized.